Environmentally friendly synthesis of nanoporous silica materials using quercetin as a morphogenetic agent - A.R. Zare Hoseinabadi; E. Rafiei Taqanaki; S. Hafez Ghoran; A.M. Amani; H. Kamyab; A. Razmfarsa; E. Khalili; M. Yusuf; S. Rajendran (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: The synthesis of mesoporous silica nanoparticles using non-surfactant agents is gaining popularity owing to the easier purification and lower toxicity of this method compared to traditional surfactant-based ones. The potential of mesoporous silica nanoparticles as advanced nanocarriers for health-related applications is increasingly recognized. Quercetin, a potent free-radical scavenging antioxidant that relies heavily on the intracellular supply of reduced glutathione, has garnered significant interest in the scientific community. In spite of recent progress, the mechanisms underlying the development of the porous framework have largely gone unexplored. The primary aim of this study is to explore the feasibility of utilizing quercetin as a template for the synthesis of mesoporous silica nanoparticles, circumventing the need for conventionalMETHODS: This research investigates the impact of the chemical structure and properties of polyphenols, specifically quercetin, on their templating potential. The study reveals the arrangement of quercetin, which acts as a model for the development of mesoporous silica nanoparticles, forming a supramolecular structure that facilitates silica binding. The composition of this supramolecular framework leads to unconventional and variable pore structures. The scanning electron microscopy, transmission electron microscopy, Fourier-transform infrared spectroscopy, x-ray diffraction analysis, energy-dispersive X-ray spectroscopy, and Brunauer–Emmett–Teller analysis were used to characterize the quercetin-templated mesoporous silica nanoparticles and provide detailed insights into their morphology.FINDINGS: The results from the viability test and antiviral assays demonstrated that quercetin-templated mesoporous silica nanoparticles are non-toxic and possess inhibitory and antiviral properties that are comparable to those of Oseltamivir, which served as a positive control. Quercetin served as a non-surfactant, neutral template in an ammonia and ethanol mixture, resulting in approximately spherical particles with monodisperse diameters of about 180 nanometers. These nanoparticles of mesoporous silica showed a concentration-dependent efficacy in inhibiting pathogenic microorganisms. In x-ray diffraction pattern for Mesoporous silica nanoparticles, a number of Bragg's reflections referring to the (111), (200), and (220) sets of lattice planes were detected, which can be described by the fundamental face center cubic structure of mesoporous silica nanostructures. Because of the smaller particle diameter impact and incomplete internal structure of the nanostructures, the intense peak at 2θ= 24 degrees demonstrated the silica peak, which reflected crystalline nature. According to calculations based on the Brunauer–Emmett–Teller method, the specific surface area of Quercetin-templated mesoporous silica nanoparticles was determined to be 55.227 cubic meters. Furthermore, the Barrett-Joyner-Halenda analysis provided measurements of the pore size at 24.312 nm and the pore volume at 0.336 square centimeters per gram, respectively.CONCLUSION: The study results outcomes demonstrated that quercetin forms a macromolecular scaffold that functions as a template for the formation of mesoporous silica nanoparticles. The irregular pore structure observed is attributed to the unique characteristics of quercetin. Using small-angle X-ray scattering, detailed information was obtained regarding the constituents and the porous nature of the resulting mesoporous silica nanoparticles. This study reveals innovative insights into the mechanisms by which the macromolecular structure of the template governs the dimensions of particles and the process of pore formation. The role of quercetin in the morphogenetic development of mesoporous silica nanoparticles has been thoroughly investigated. In addition, quercetin-templated mesoporous silica nanoparticles exhibited significant antioxidant properties, akin to butylated hydroxytoluene, and showed great potential for various clinical applications.